Recenzja książki Małgorzaty Bruder i Janusza Deglera, «Budynki i wnętrza teatrów w Europie na dawnej pocztówce z kolekcji Janusza Deglera» - Jarosław Komorowski (Pamiętnik Teatralny, 2017)
A review of the Polish–English catalogue of Professor Degler’s postcards collection. In the Henryk Tomaszewski Museum of Theatre that opened in Wrocław on 26–27 March 2017, among other exhibitions devoted to outstanding individuals, there is also The Study of Professor Janusz Degler, which houses the library donated to the Museum by the professor who is a theatre and Witkacy scholar of international renown. And it is here that Professor Degler’s collection of postcards—or more precisely, a carefully selected part of it, a few hundred of several thousand items—has been displayed. This part of the collection is also presented in the wonderfully edited Polish–English catalogue with colour reproductions of the exhibits. There are exactly 597 of them, and additional two in the introductory part. The book takes us on a marvellous journey to the most distant theatrical corners of Europe. We travel from Paris to Petersburg in a blink of an eye. The images change in quick succession, as if in a kaleidoscope: theater houses great and small, of brick and of wood, historically significant and completely forgotten. The authors of the catalogue rightly boast that it is the first publication in the world to present a unique collection of old postcards displaying theatre architecture.